O fake nas mídias: simulações irônicas - Emérito, Matheus Barbosa (2012)
This research deals with a study about photographic fake that have increasingly present in the media and advertising world of the XXI century. The term fake is used both to define false objects the really try to mistake people, and others which only simulate and have no intention to deceive as a priority. In order to prove the potential of the photographic fake as a critical element of media, even being part of it, so this work made a distinction between the concepts of forgery and simulation. The fake photographs or the ones produced as simulations are considered as devices for reflection elements of the production process itself or its representation as an element of culture. Through consideration of the studies of Hans Tietze and Nelson Goodman, it was observed that faking is a cultural practice that exists since the middle age. This practice is quite common in human social behavior, is directly related to the concepts of identity, originality and authenticity, concepts treated by Umberto Eco, who guided the approach about the false in this thesis. On the other side, there is the fake as simulation that uses the parody to promote critics. Through the studies of Linda Hutcheon, who gives the parody an ironic characteristic, this work defines one side of the fake as a parodic and ironic simulation. It was considered then as a corpus, a set of parody models: Not the Financial Times, which criticizes the traditional printed The Financial Times through imitation; BC Byte Series, archaeological work that relates the fictional work of art with the artefact; Esquire magazine, which publishes fiction news, among others. By selecting a diverse group, we verified that some examples present the hints that are responsible by the construction of the parodic sense in a concealed mode. So, a parody becomes a mock and determines the parodic and radical simulation. While examining the diverse photographic material chosen, it was observed that the manipulations are applied as forgeries, ironic or radical parodic simulations. The parodic radical simulative photography is pointed out through the analysis of photographer Joan Fontcuberta s works, who designs faked photographs of animals, vegetables and even photo biographies. It is clear, therefore, the existence of a critical reflection on the creative process and the nature of truth that, traditionally, is the ethos of photography. The concepts and the classification presented, together with the analysis, seek to highlight the importance of proper fake as ironic parody of reflective media, continuing dissertation The fake documentary, previous research by this author